Prevalence of tet(X4) in Escherichia coli From Duck Farms in Southeast China - Yu, Yang; Cui, Chao-Yue; Kuang, Xu; Chen, Chong; Wang, Min-Ge; Liao, Xiao-Ping; Sun, Jian; Liu, Ya-Hong (Frontiers in Microbiology, 2021)
Objectives Carbapenems, colistin, and tigecycline are critically important antibiotics in clinics. After the global appearance of blaNDM and mcr mediating the resistance to carbapenems and colistin, respectively, tigecycline becomes the last-resort drug against severe human infections caused by multidrug-resistant bacteria. Recently, a mobile tigecycline resistance gene tet(X4) has been identified in Escherichia coli, Klebsiella pneumoniae, and Acinetobacter baumannii that causes high resistance to tigecycline and other tetracyclines. In this study, the prevalence of tet(X4) in E. coli isolates from duck and goose farms in Southeast China was identified and characterized. Methods Feces, soil, sewage, and dust samples were collected from duck and goose farms along with the southeast coast provinces of China. Antimicrobial susceptibility testing and polymerase chain reaction screening were performed to investigate the phenotype and genotype of tigecycline resistance. Conjugation, S1 pulsed-field gel electrophoresis (PFGE), and whole-genome sequencing were used to determine the transferability, genetic location, and the genomic characteristics of tet(X4). Results In total, 1,716 samples were collected, and 16 isolates (0.9%) recovered from Guangdong, Shandong, and Jiangsu were positive for tet(X4) gene with tigecycline minimum inhibitory concentrations ≥16 mg/L. Notably, among these tet(X4)-positive E. coil isolates, seven of them were from the environment samples (soil and sewage). PFGE and multilocus sequence typing demonstrated that ST3997 was the most prevalent sequence type (eight isolates, 50%) in Jiangsu province. By conjugation assays, 11 isolates were able to transfer tet(X4) plasmid to E. coli C600 recipient, and these plasmids belonged to IncHI1 and IncX1 detected by sequence analysis. tet(X4) was found adjacent to an insertion sequence ISCR2 downstream and a catD gene upstream for all isolates. In addition, multiple-drug resistance to tigecycline, chlortetracycline, ampicillin, florfenicol, ciprofloxacin, gentamicin, trimethoprim/sulfamethoxazole, and fosfomycin was profiled in most of the tet(X4)-positive isolates. Conclusion The identification of tet(X4) harboring E. coli strains in duck farms and their surrounding environment enlarges our knowledge of the variety and prevalence of tigecycline resistance. The prevalence of tet(X4) raises concern for the use of tetracyclines in animal farming, and the tet(X4) gene should be listed as primary gene for resistance surveillance.